2011
DOI: 10.2319/032910-173.1
|View full text |Cite
|
Sign up to set email alerts
|

From 2D to 3D: an algorithm to derive normal values for 3-dimensional computerized assessment

Abstract: Objective: To test the accuracy of a mathematical model (algorithm) that corrects measurements made on conventional lateral head films to corresponding dimensions observed in a cone beam computed tomography (CBCT) scan in human subjects. Materials and Methods: Thirteen subjects had lateral cephalograms taken with a conventional cephalometric machine as well as a CBCT scan. Measurements of midface length, mandibular length, and lower anterior face height (LAFH) from both examinations were calculated. Two other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 24 publications
1
32
0
2
Order By: Relevance
“…In addition, trained radiologists are often required for the interpretation of CT images, which further reduces its use in routine orthodontic practice. 11,12 Any flaws in predictability, prevention and early diagnosis of this condition, especially in cases of extensive RR, can cause drastic consequences to both orthodontic treatment and patient's health. It is therefore important to determine the magnitude and prevalence of RR in various populations, as well as related risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, trained radiologists are often required for the interpretation of CT images, which further reduces its use in routine orthodontic practice. 11,12 Any flaws in predictability, prevention and early diagnosis of this condition, especially in cases of extensive RR, can cause drastic consequences to both orthodontic treatment and patient's health. It is therefore important to determine the magnitude and prevalence of RR in various populations, as well as related risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, its values of Co-A, Co-Gn equal the projection of each 3D measurement on the midsagittal plane. 6 It was found that the distances of this type were comparable between them as well, after adjustment by the specific magnification. Generally, these comparative results of both Types 1 and 2 are consistent with those of our study.…”
Section: 16mentioning
confidence: 90%
“…In the light of trigonometric functions, the values of Co-A, Co-Gn on the conventional cephalogram equal the projection of each 3D measurement on the midsagittal plane multiplying the midsagittal magnification. Based on this principle, Gribel et al 6 rectified the measurements made on conventional lateral films to corresponding dimensions observed in CBCT scans in human subjects.…”
Section: 16mentioning
confidence: 99%
See 2 more Smart Citations